Pengaruh Konten Youtube Akademi Crypto Terhadap Pengetahuan Terkait Crypto (Survey Kepada Anggota Komunitas Academy Cryptocurrency) - Roy Adi Prastyo; Haloho, Heppy (Research and Community Service UNIVERSITAS KALBIS, 2026)
This study aims to determine the effect of Cryptocurrency Academy YouTube content on the knowledge of Cryptocurrency Academy community members. This study used a quantitative approach with a survey method and the Stimulus–Response (S–R) theory as a theoretical framework to analyze the effect of content exposure on the audience's level of knowledge. The research population includes members of the Cryptocurrency Academy community aged 20–40 who watch Cryptocurrency Academy YouTube content. Data were collected by distributing questionnaires to respondents who met the research criteria. The results of the analysis show that the quality of accurate information, the credibility of the sources, and an interesting delivery style contribute to increasing the cryptocurrency knowledge of community members. These findings confirm that YouTube educational content has a significant influence on the public's understanding of digital finance. The research hypothesis was accepted, with a Pearson correlation value of r = 0.876, indicating a very strong relationship.